Institutional provisions for administration of rural development programmes: experience from Fadama 111 development programme in Taraba state, Nigeria - Dimelu, MU; Bonjoru, FH; Emodi, AI; Madukwe, MC (International Journal of Agricultural Research, Innovation and Technology, 2015)
The study examined institutional provisions in the implementation of Fadama 111 Development Project in Taraba State, Nigeria during 2008-2013. All the staff of the project (57) from eight out of 16 local government areas participated in the programme was used in the study. Data were collected with questionnaire and analysed using descriptive statistics. The results showed strong linkages of the state Fadama coordinating office with government parastaltals and organizations at different levels of the project implementation. There were strong adherence to rules and regulations guiding staff recruitment, financial management, preparation of local development plan, environmental compliance and friendliness, and group formation. The project was constrained by several institutional factors namely delay in the payment of counterpart fund by the government (M=3.39), lack of transport and other logistic supports (M=3.06), lack of payment of counterpart fund by the government (M=3.04) and others. The study recommends that policy makers and development planner should ensure functional mechanisms that could foster and enhance linkages, and support adherence to rules and regulations prescribed for implementation of development programmes. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22644 Int. J. Agril. Res. Innov. & Tech. 4 (2): 29-34, December, 2014